Preparation method of electrode grid line and photovoltaic cell

Through hot pressing technology, the groove template and flat plate coating technology are produced, combined with water-soluble polymer layer and high-temperature sintering, the resolution and cost problems in photovoltaic cell electrode gate line printing technology are solved, and high-efficiency and low-cost electrode preparation is achieved , improving photoelectric conversion efficiency and production efficiency.

CN119208453APending Publication Date: 2024-12-27BEIJING ZENITHNANO TECH CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411372762.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing photovoltaic cell electrode grid line printing technology is difficult to achieve high resolution, low cost and simple process, resulting in production efficiency and material waste.

Method used

Hot pressing technology is used to produce groove templates and flat plate coating technology. Through the water solubility and high-temperature sintering of the polymer layer, transfer of high-resolution electrode patterns and uniform filling of conductive materials are achieved, simplifying the production process.

Benefits of technology

It improves the fineness and consistency of the electrode gate lines, reduces material waste, improves photoelectric conversion efficiency and production efficiency, reduces manufacturing costs, and ensures the stability and reliability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208453A_ABST
    Figure CN119208453A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an electrode grid line and a photovoltaic cell, and relates to the field of photovoltaic technology, and the preparation method comprises the following steps: S1, providing a substrate, and forming a polymer layer on the substrate; s2, pressing a groove corresponding to a required electrode pattern on the polymer layer by using a mold to obtain a template; s3, a conductive material is smeared on the polymer layer, the groove is filled with the conductive material, and the redundant conductive material is scraped off; s4, providing a base material, covering the base material with the template, and transferring the polymer layer and the conductive material to the base material at a certain temperature and pressure; s5, stripping the substrate from the polymer layer, dissolving the polymer layer, and leaving the conductive material to be adhered to the base material; and S6, sintering the conductive material to form the electrode grid line. According to the invention, plate coating, high-precision transfer printing, water dissolution and high-temperature sintering technologies are utilized, the production process is efficient, and the accuracy of electrode patterns can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic technology, and in particular to a method for preparing an electrode grid line and a photovoltaic cell. Background Art

[0002] As the new power system dominated by new energy is being deployed at an accelerated pace, the status of the photovoltaic industry has been significantly improved, ushering in a historic opportunity. As the core component of the photovoltaic system, the industrial production of solar cells is mainly based on single-crystal silicon cells, accounting for more than 90% of the total output. As a key component of solar cells, the electrode grid has an important impact on its performance. Optimizing the electrode grid can effectively improve the photoelectric conversion efficiency.

[0003] In the manufacturing process of photovoltaic cells, the printing technology of electrode grid lines is a key production process. Existing electrode grid line printing technologies include screen printing, inkjet printing, offset printing and flexible printing. Among them, screen printing technology is widely used in photovoltaic cell production. Conductive paste (such as silver paste) is printed onto silicon wafers through a screen to form an electrode pattern. Although the screen printing process is mature, the production cost is low and it is suitable for large-scale industrial production, it is difficult to achieve high-resolution fine patterns, resulting in excessively wide electrode line widths, reduced light absorption, increased silver paste usage, and high cleanliness requirements. In addition, the screen printing production speed is slow, which affects production efficiency.

[0004] As a non-contact printing technology, inkjet printing uses a nozzle to accurately spray conductive ink onto the battery surface to form an electrode pattern. This technology can achieve higher resolution and finer electrode patterns, reduce the shading area, improve the photoelectric conversion efficiency, and reduce the waste of conductive paste. However, inkjet printing technology has high requirements for equipment and processes, especially the accuracy and durability of the nozzle, as well as the rheological properties of the ink, which need to be further optimized to meet the needs of large-scale production.

[0005] Offset printing technology transfers the conductive paste to the cell surface through a rubber cloth roller, which is suitable for printing high-precision and complex patterns. Flexographic printing uses a flexible printing plate for large-area continuous printing, which is suitable for the manufacture of thin-film solar cells or flexible photovoltaic modules. Although offset and flexible printing have advantages in resolution and pattern complexity, their processes are relatively complex, and the equipment and operating costs are high. They are currently mainly used in specific types of photovoltaic cells and have not yet been widely used in mainstream silicon-based solar cells.

[0006] Therefore, developing a photovoltaic cell electrode grid line printing technology with simple process, low cost and high resolution is an important issue that needs to be solved urgently. Summary of the invention

[0007] In order to develop a photovoltaic cell electrode grid line printing technology with simple process, low cost and high resolution, the present application provides an electrode grid line preparation method and a photovoltaic cell.

[0008] The present application provides a method for preparing an electrode grid line and a photovoltaic cell using the following technical solutions: A method for preparing electrode grid lines, comprising the following steps: S1, providing a substrate, and forming a polymer layer on the substrate; S2, using a mold to press out grooves corresponding to the required electrode pattern on the polymer layer to obtain a template; S3, applying a conductive material on the polymer layer so that the conductive material fills the grooves, and scraping off excess conductive material; S4, providing a substrate, covering the template on the substrate, and transferring the polymer layer and the conductive material to the substrate under a certain temperature and pressure; S5, peeling off the substrate and the polymer layer, and dissolving the polymer layer, leaving the conductive material adhering to the substrate; S6, sintering the conductive material to form the electrode grid lines.

[0009] By adopting the above technical scheme, a high-resolution electrode pattern can be achieved by using a groove template formed by hot pressing, making the electrode grid lines more refined and consistent, thereby improving the photoelectric conversion efficiency; the application of flat-plate coating technology allows the conductive material to evenly fill the grooves and scrape off excess material, thereby reducing material waste; the pressure and temperature during the transfer process ensure that the conductive material is accurately transferred and attached to the substrate, maintaining the accuracy of the electrode pattern; compared with traditional electrode preparation processes, the method of the present application simplifies the production process, reduces multiple complex steps and equipment requirements through flat-plate coating and hot pressing technology, and through flat-plate coating technology, transfer, water dissolution and high-temperature sintering, the production process is more efficient and can support large-scale production needs. The high-temperature sintering step ensures the stability and durability of the conductive material, thereby improving the reliability and performance of the electrode.

[0010] In a specific embodiment, the glass transition temperature of the polymer layer is 70-100° C., and the material of the polymer layer includes a water-soluble polymer material.

[0011] By adopting the above technical solution, the polymer layer is soluble in water, making the coating and film-forming process more convenient without the need for complicated solvent treatment; and the water-soluble property makes the polymer layer easy to clean after use, reducing the burden on the environment.

[0012] In a specific embodiment, the water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.

[0013] In a specific embodiment, the thickness of the polymer layer is 5-20 μm, and the opening width of the electrode pattern is 3-10 μm.

[0014] By adopting the above technical solution and utilizing the above parameter design, this thickness range can balance the strength, flexibility and conductivity of the polymer layer and is suitable for a variety of application requirements. The thin layer design helps to reduce material waste and makes it suitable for microstructures. The electrode pattern opening width in this range can take into account the subsequent filling efficiency of the conductive material and the requirements for the dimensional accuracy of the electrode grid lines. The narrower opening width helps to reduce the parasitic resistance between the electrode grid lines and improve the current collection efficiency of the battery. At the same time, within this width range, it can also ensure that the conductive material can be fully and evenly filled into the opening to avoid the generation of voids or defects. By precisely controlling the thickness of the polymer layer and the width of the patterned opening, the dimensional accuracy of the electrode grid lines can be significantly improved, which helps to reduce performance fluctuations and defective product rates caused by dimensional deviations.

[0015] In a specific embodiment, the conductive material includes silver paste, the silver paste includes a binder, and the binder is a phenolic resin or an epoxy resin.

[0016] By adopting the above technical solution and utilizing the design of the adhesive, the binding force between the silver particles in the silver paste can be effectively enhanced, thereby reducing the interruption of the conductive path in the silver paste and improving the conductivity; and it can also promote the adhesion between the silver paste particles and the substrate, improve the bonding strength between the conductive layer and the substrate, further optimize the conductive performance, and at the same time improve the overall durability and reliability.

[0017] In a specific embodiment, in S2, the groove is formed on the polymer layer by hot pressing at a temperature of 90-150°C.

[0018] By adopting the above technical solution, at an appropriate hot pressing temperature, the polymer layer can be better shaped to form a precise groove shape, thereby improving processing accuracy and finished product quality, and avoiding discoloration and embrittlement of the polymer layer during the hot pressing process, thereby ensuring the stability and uniformity of the material.

[0019] In a specific embodiment, in S4, a pressure of 2-20 MPa is applied to make the conductive material adhere to the substrate.

[0020] The above technical solutions can help ensure good contact between the conductive material and the substrate while avoiding material damage or performance problems that may be caused by excessive pressure. The specific pressure value may need to be optimized according to the actual application and material properties.

[0021] In a specific embodiment, in S5, the polymer layer is dissolved using water at room temperature.

[0022] By adopting the above technical solution, the characteristics of water dissolution at room temperature make the process operation simpler, and do not require high-temperature equipment or special conditions, thereby reducing production costs. In addition, the water dissolution process is more environmentally friendly and friendly to the operating environment. This method also reduces compatibility issues with other materials because water dissolution at room temperature will not cause adverse reactions between materials.

[0023] In a specific embodiment, in S6, the conductive material is sintered at a high temperature of 500-1000°C.

[0024] By adopting the above technical solution and the above parameter design, the sintering time can be shortened, while ensuring that the conductive material forms a solid electrode grid line and improves the conductive performance.

[0025] In a specific embodiment, the longitudinal cross-section of the groove is in the shape of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, or a polygon.

[0026] By adopting the above technical solution, the longitudinal cross-sectional design of the above shape helps to change the incident and refraction paths of light, can better capture and guide light, can effectively reduce light reflection losses, so that more light is absorbed by semiconductor materials and converted into electrical energy, thereby improving photoelectric conversion efficiency.

[0027] In a specific embodiment, the material of the substrate includes one of polyethylene terephthalate, polyimide, polyethylene terephthalate copolymer, polycarbonate, polypropylene, and polyurethane, and the thickness of the substrate is 120-200 μm.

[0028] By adopting the above technical solution, the above material has higher strength and toughness, provides good structural support and durability, has good tolerance to various chemical substances, and can remain stable in various environments.

[0029] In a specific embodiment, the substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

[0030] By adopting the above technical solution, the above material has good electronic conductivity and stability, and has good thermal stability and thermal conductivity, and is suitable for the manufacture of various electronic devices.

[0031] In a specific implementation manner, the material of the mold is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy.

[0032] A photovoltaic cell comprises the electrode grid lines prepared by the preparation method described above.

[0033] By adopting the above technical solution, the photovoltaic cell with electrode grid lines made by this preparation method can significantly improve the photoelectric conversion efficiency of the photovoltaic cell, reduce manufacturing costs, improve production efficiency, and ensure the long-term stability and reliability of the cell through high-precision pattern transfer, excellent electrode quality, simplified process flow and optimized electrode design, which will help promote the application and development of photovoltaic cells.

[0034] In a specific possible implementation manner, the longitudinal cross-section of the electrode grid line is a triangle, a trapezoid or a semi-ellipse, the top angle of the triangle is 20°-60°, the height of the triangle is 10±2μm, and the aspect ratio of the triangle is 2:1, the base angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2μm, and the aspect ratio of the trapezoid is 2:1, the height of the semi-ellipse is 10±2μm, and the aspect ratio of the semi-ellipse is 2:1.

[0035] By adopting the above technical solution, the electrode grid lines designed with the above vertex angle parameters, the triangular, trapezoidal, and semi-elliptical edges can better control the propagation direction of light, reduce reflection losses, increase light absorption, and help increase the path length of light inside the battery, thereby increasing light absorption efficiency.

[0036] In a specific embodiment, the triangle is an isosceles triangle, the trapezoid is an isosceles trapezoid, and the ellipse is a symmetrical semi-ellipse.

[0037] By adopting the above technical solutions, isosceles triangles, isosceles trapezoids, and symmetrical semi-ellipses can evenly distribute light on the electrode surface, which can not only reduce the use of conductive materials, but also reflect and utilize more light energy, reduce the concentration effect of light, thereby improving the light capture efficiency, and helping to achieve a more uniform current distribution, reduce local resistance, and improve the current output efficiency of the battery. It can also provide better structural stability, which helps to maintain the mechanical strength and long-term reliability of the electrode.

[0038] In summary, the present application includes at least one of the following beneficial technical effects: the present application utilizes a groove template and a triangular electrode pattern design produced by hot pressing technology to achieve a high-resolution electrode pattern, thereby making the electrode grid lines more refined and consistent, significantly improving the photoelectric conversion efficiency; the application of flat-plate coating technology ensures that the conductive material uniformly fills the grooves and effectively scrapes off excess material, thereby reducing material waste; in addition, during the transfer process, by applying pressure, the conductive material can be accurately transferred to the substrate, maintaining the accuracy of the electrode pattern, thereby improving the uniformity and stability of the electrode and ensuring excellent electrical performance; compared with traditional electrode preparation processes, the present method simplifies the production process, reduces multiple complex steps and equipment requirements, and by combining technologies such as flat-plate coating, high-precision transfer, water dissolution and high-temperature sintering, the production process becomes more efficient and can meet the needs of large-scale production. The high-temperature sintering step further ensures the stability and durability of the conductive material and improves the reliability and performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the process flow of the method for preparing the electrode grid line of Example 1 of the present application.

[0040] Figure 2 It is a schematic diagram of the process flow of the method for preparing the electrode grid lines of Example 2 of the present application.

[0041] Figure 3 It is a schematic diagram used to show the longitudinal cross-sectional shape of the electrode grid line.

[0042] Explanation of the reference numerals: 1. substrate; 2. polymer layer; 3. groove; 4. template; 5. conductive material; 6. base material; 7. mold; 8. electrode grid line. DETAILED DESCRIPTION

[0043] The following is combined with Figure 1 This application is described in further detail.

[0044] Example 1 Reference Figure 1 The present application discloses a method for preparing an electrode grid line, the method comprising the following steps: S1. Provide a substrate 1, and form a polymer layer 2 on the substrate 1. In this process, it is necessary to ensure that the surface of the substrate 1 is clean and flat to ensure the quality of the subsequent coating process, and perform surface treatment on the substrate 1 to enhance the adhesion of the polymer layer 2. The thickness of the substrate 1 is 120-200 μm. In this embodiment, preferably, the thickness of the substrate 1 is 150 μm. The material of the substrate 1 includes but is not limited to one of polyethylene terephthalate (PET), polyimide (PI), polyethylene terephthalate glycol copolymer (PETG), polycarbonate (PC), polypropylene (PP), and polyurethane (PU). In this embodiment, preferably, the material of the substrate 1 is polyimide. Polyimide has good heat resistance and can withstand high temperatures up to 400°C. It has high strength and toughness, provides good structural support and durability, and has good tolerance to a variety of chemical substances and can remain stable in a variety of environments. Before coating, the substrate 1 is subjected to necessary pretreatment, and the pretreatment method includes cleaning, drying and surface activation, and these steps are intended to remove pollutants on the surface of the substrate 1, increase the surface roughness, and improve the adhesion of the polymer layer 2; In this embodiment, a polymer layer 2 is formed on the substrate 1 by using a flat coating technology, including but not limited to; specifically, a uniform polymer solution is coated on the substrate 1, and the uniformity and thickness of the coating are controlled. After the coating is completed, the polymer layer 2 is dried or cured under an environmental condition of 50°C - 70°C to ensure that its physical and chemical properties meet the requirements. In this embodiment, according to the properties and application requirements of the polymer, further drying treatment can be performed, including but not limited to heating in an oven, so that the polymer layer 2 is further hardened for long-term storage; The thickness of the polymer layer 2 is 5-20 μm. In this embodiment, preferably, the thickness of the polymer layer 2 is 10±2 μm. The polymer layer 2 of this thickness can balance strength, flexibility and conductivity, and is suitable for a variety of application requirements. The thin layer design of the polymer layer 2 helps to reduce material waste and makes it suitable for high-density integrated electronic devices or microstructures. In the present embodiment, the glass transition temperature of the polymer layer 2 is 70-100° C. The material of the polymer layer 2 includes but is not limited to a water-soluble polymer material, and the water-soluble polymer material includes but is not limited to one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile. In the present embodiment, preferably, the water-soluble polymer material is polyvinyl alcohol, which may change color and become brittle when heated to above 150° C. Polyvinyl alcohol is insoluble in gasoline, kerosene, vegetable oil, benzene, toluene, ethylene dichloride, carbon tetrachloride, acetone, ethyl acetate, methanol, ethylene glycol and other organic solvents; polyvinyl alcohol is soluble in water, making the coating and film-forming process more convenient without the need for complicated solvent treatment, and the water-soluble property makes polyvinyl alcohol easy to clean after use, reducing the burden on the environment; In this embodiment, the water solubility of polyvinyl alcohol can be changed by adjusting the alcoholysis degree of polyvinyl alcohol or performing a blending modification method so that it can be quickly dissolved at room temperature; Specifically, increasing the alcoholysis degree of polyvinyl alcohol (i.e., the degree of alcoholysis of polyvinyl alcohol) can increase its dissolution rate in water, causing it to be more easily penetrated and dissociated by water molecules, thereby accelerating the dissolution process; blending polyvinyl alcohol with other water-soluble polymers or additives can improve its water solubility. For example, blending with hydrophilic polymers can enhance the solubility and dissolution rate of polyvinyl alcohol. By optimizing the blending ratio and selecting appropriate modifiers, the solubility properties of polyvinyl alcohol can be adjusted to meet specific application requirements.

[0045] S2. Using hot pressing technology, a mold 7 is used to hot press a groove 3 corresponding to the desired electrode pattern on the polymer layer 2 to obtain a template 4. In this embodiment, the material of the mold 7 includes but is not limited to one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy. The polymer layer 2 includes but is not limited to forming a groove 3 corresponding to the electrode pattern by hot pressing with a hot press; In this embodiment, the opening width of the electrode pattern of the polymer layer 2 is 3-10 μm, and the aspect ratio is 2:1, that is, the notch width of the groove 3 is 3-10 μm, and the aspect ratio is 2:1; in the precision process of preparing the solar electrode grid line 8, it is very important to accurately control the thickness of the electrode grid line 8 and the width of the patterned opening. These two parameters directly affect the subsequent filling effect of the conductive material 5, the dimensional accuracy of the electrode grid line 8 and the final performance of the battery; the thickness of the polymer layer 2 is in the range of 5-20 μm, and the width of the electrode patterned opening is in the range of 3-10 The aspect ratio is within the range of 2:1 μm, and the above dimensions can take into account the subsequent filling efficiency of the conductive material 5 and the dimensional accuracy requirements of the electrode grid lines 8. The narrower opening width helps to reduce the parasitic resistance between the electrode grid lines 8 and improve the current collection efficiency of the battery. At the same time, within this width range, it can also ensure that the conductive material 5 can be fully and evenly filled into the opening to avoid the generation of voids or defects. By precisely controlling the thickness of the polymer layer 2 and the width of the patterned opening, the dimensional accuracy of the electrode grid lines 8 can be significantly improved, which helps to reduce performance fluctuations and defective product rates caused by dimensional deviations.

[0046] In this embodiment, the hot pressing temperature of the polymer layer 2 is 90-150° C. Preferably, the best hot pressing molding conditions are: hot pressing temperature of 130° C., hot pressing pressure of 10 MPa, and hot pressing time of 2 min. Under these conditions, the groove 3 can be well hot pressed. Specifically, the dried polymer layer 2 is placed on a hot press. According to the characteristics of the polymer layer 2 and the accuracy of the required electrode pattern, the temperature of the hot press is set to 130°C, the pressure is set to 10MPa and the time is set to 2min. The temperature can soften the polymer layer 2, the pressure can ensure that the pattern of the mold 7 on the hot press can be fully high-precision embossed, and the time can ensure that the details of the pattern are accurately replicated. The dried polymer layer 2 is placed on the heating plate of the hot press, and then the mold 7 is aligned and pressed down. The heating plate is heated to a set temperature, and the mold 7 is pressed into the polymer layer 2 under the pressure of the heating plate to form a desired electrode pattern. The corresponding groove 3 is formed in the mold 7; after the hot pressing is completed, the mold 7 and the polymer layer 2 need to be cooled to room temperature. This cooling process allows the polymer layer 2 to maintain its shape in the mold 7, so that the shape and size of the groove 3 are stabilized; after the cooling is completed, the mold 7 is carefully removed from the polymer layer 2, and the groove 3 pattern is clearly visible and matches the required electrode pattern; the template 4 after hot pressing is carefully checked to confirm whether the size and shape of the groove 3 meet the requirements of the micron-level or even nano-level electrode pattern. If necessary, the template 4 is post-processed, for example, the template 4 can be cleaned to remove residues, or further refined to meet the requirements of subsequent processes.

[0047] In this process, the hot pressing temperature range is above the glass transition temperature of polyvinyl alcohol and below its melting point, so as to avoid discoloration and embrittlement of the polymer layer 2 during the hot pressing process, thereby ensuring the processability, stability and uniformity of the material; under the above-mentioned optimal hot pressing molding conditions, the polymer layer 2 can be better shaped to form a precise groove 3 shape, thereby improving the processing accuracy and the quality of the finished product; by controlling the hot pressing temperature within a safe range, the thermal stress caused by excessive temperature is reduced, thereby reducing the thermal damage of the material; The shape and size of the groove 3 correspond to the electrode grid line 8. In actual operation, the size and shape of the electrode grid line 8 to be transferred are controlled to reduce the ohmic loss of the electrode grid line 8. The longitudinal cross-sectional shape of the groove 3 includes but is not limited to one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon. In the present embodiment, preferably, the longitudinal cross-sectional shape of the groove 3 is a triangle. The triangular longitudinal cross-sectional design helps to change the incident and refraction paths of light, can better capture and guide light, can effectively reduce the reflection loss of light, so that more light is absorbed by the semiconductor material and converted into electrical energy, thereby improving the photoelectric conversion efficiency.

[0048] S3, using a flat coating technique, applying a conductive material 5 on the polymer layer 2, so that the conductive material 5 fills the groove 3, and scraping off excess conductive material 5; Specifically, on the polymer layer 2 where the groove 3 has been formed, the conductive material 5 is evenly applied by a flat coating technology. A suitable conductive material 5 is selected and applied by a flat coating machine or a scraping tool. The conductive material 5 is evenly applied on the polymer layer 2 to ensure that the material can fully fill all the gaps in the groove 3 and cover the entire surface. After coating, a scraper or other tool is used to scrape off excess conductive material 5 on the surface to ensure that the conductive material 5 in the groove 3 is flat and tightly combined with the polymer layer 2. The conductive material 5 includes but is not limited to silver paste, the components of the silver paste include an adhesive, the adhesive is a phenolic resin or an epoxy resin, and the adhesive is used to enhance the bonding between the particles of the silver paste. In this embodiment, the shear strength of the adhesive is 10-30 MPa, and it has excellent bonding performance and chemical resistance; The design of the adhesive can effectively enhance the bonding force between the silver particles in the silver paste, thereby reducing the interruption of the conductive path in the silver paste and improving the conductivity; The polymer layer 2 of polyvinyl alcohol is incompatible with the binder of the silver paste and is non-reactive; the non-reactivity ensures that no chemical change or degradation occurs between the polyvinyl alcohol and the silver paste, and the performance of each of the two is kept stable, which can ensure that each material performs best in its intended application and avoids mutual influence; and the polymer layer 2 can be easily removed by water solubility after processing without affecting the performance of the silver paste; S4, covering the template 4 on the substrate 6, the polymer layer 2 and the conductive material 5 are adhered to the substrate 6 under a certain temperature and pressure. In this process, including but not limited to, the polymer layer 2, the conductive material 5 and the substrate 6 are adhered and attached by a high temperature of 90-150°C and a pressure of 2-20MPa. In this embodiment, preferably, the best hot pressing transfer conditions are: hot pressing temperature of 130°C, hot pressing pressure of 10 MPa, and hot pressing time of 8min. Under this condition, the conductive material 5 and the polymer layer 2 can be well adhered to the substrate 6, the shape of the conductive material 5 is complete and without deformation, and the polymer layer 2 and the substrate 1 can be well peeled off; Specifically, clean the surface of the substrate 6 to remove any contaminants or particles, ensure that the surface of the substrate 6 is clean and flat, cover the template 4 coated with the conductive material 5 on the substrate 6, accurately align the template 4 with the substrate 6, ensure that the pattern of the template 4 is aligned with the position on the substrate 6, and use an alignment tool or a visual alignment system to improve the alignment accuracy. Gently place the template 4 on the substrate 6 to ensure that each part of the conductive material 5 of the template 4 is in close contact with the surface of the substrate 6. Apply a pressure of 10 MPa and a hot pressing temperature of 130°C to press the template 4 onto the substrate 6. The pressure needs to be evenly distributed to ensure that the conductive material 5 is fully attached and a clear pattern is formed. This step requires ensuring that the pressure is evenly applied to ensure accurate transfer of the conductive material 5. After applying the pressure, maintain the hot pressing between the template 4 and the substrate 6 for 8 minutes to ensure that the conductive material 5 is fully in contact with and adheres to the substrate 6. In this embodiment, the adhesive can also enhance the bonding between the silver paste particles of the conductive material 5 and the substrate 6. After hot pressing transfer, the conductive material 5 and the polymer layer 2 will adhere tightly to the substrate 6, and the substrate 1 on the other side can be easily peeled off from the substrate 1. The adhesive in the silver paste can promote the adhesion between the silver paste particles and the substrate 6, thereby improving the bonding strength between the conductive material 5 and the substrate 6, further optimizing the conductive performance, and at the same time improving the overall durability and reliability.

[0049] S5, peeling off the substrate 1 and the polymer layer 2, and dissolving the polymer layer 2, leaving the conductive material 5 adhered to the substrate 6; the substrate 6 includes but is not limited to one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate. In this embodiment, preferably, the substrate 6 is a polycrystalline silicon substrate. The polycrystalline silicon substrate has good electronic conductivity and stability, and has good thermal stability and thermal conductivity, and is suitable for the manufacture of various electronic devices, and can be used in the photovoltaic cell applied in this application; Specifically, after the transfer work is completed, the substrate 1 and the polymer layer 2 are first peeled off, and then the polymer layer 2 is dissolved using water at room temperature. In this embodiment, the temperature of the water at room temperature includes but is not limited to 20-25°C. After the substrate 1 is peeled off, first, the polymer layer 2 coated with the conductive material 5 is immersed in a container containing water at room temperature. The water temperature should be maintained at room temperature 20-25°C to avoid thermal damage to the conductive material 5 or the substrate 6. During the immersion process, the polymer layer 2 will gradually dissolve in the water. In order to ensure that the polymer layer 2 is completely dissolved, the water can be stirred appropriately or the water temperature can be increased to promote the uniform dissolution process. The time of this process depends on the thickness and material properties of the polymer layer 2. During this period, the dissolution of the polymer layer 2 needs to be checked regularly to ensure that it is completely dissolved. When the polymer layer 2 is completely dissolved, the conductive material 5 pattern on the surface of the polymer layer 2 will be completely retained on the substrate 6; In order to further ensure the adhesion and stability of the conductive material 5, the surface of the substrate 6 can be rinsed with clean water to remove the tiny fragments of the polymer layer 2 that may remain. Finally, the transferred substrate 6 is dried in the air or by other methods to prepare for the next step of processing.

[0050] S6, sintering the conductive material 5 to form electrode grid lines 8 on the substrate 6. In this embodiment, the process includes but is not limited to sintering the conductive material at a high temperature of 500-1000° C.; Specifically, the substrate 6 coated with the conductive material 5 is placed in a heating furnace or an oven for high-temperature sintering at 500-1000°C. The temperature and time of the sintering process should be set according to the conductive material 5 to ensure that it can be fully sintered at high temperature without damaging the substrate. The sintering time should be set according to the characteristics of the conductive material 5 to ensure that the material has enough time to complete chemical reactions or physical changes at high temperatures to achieve optimal conductivity and adhesion. After sintering, the substrate 6 is allowed to cool naturally to room temperature to avoid thermal stress from damaging the electrode grid lines 8. The sintered electrode grid lines 8 are checked to ensure that their patterns are clear and well adhered. Check whether there is poor conductivity, defects or falling off to ensure that the quality of the electrode grid lines 8 meets the design requirements. During this process, if necessary, cleaning is performed to remove any residues or contaminants from the sintering process, and electrical performance testing can also be performed to verify whether the conductivity of the electrode grid line 8 meets the specifications and confirm its performance in actual applications.

[0051] The method of the present application has simple process steps, relatively low material and equipment requirements, and reduces the overall production cost; the electrode pattern of the groove 3 produced by hot pressing technology realizes a high-resolution electrode pattern, thereby making the electrode grid line 8 more refined and consistent, and significantly improving the photoelectric conversion efficiency; the application of flat-plate coating technology ensures that the conductive material 5 uniformly fills the groove 3 and effectively scrapes off excess material, thereby reducing material waste; in addition, during the transfer process, by applying pressure and temperature, it is ensured that the conductive material 5 can be accurately attached to the substrate 6, maintaining the accuracy of the electrode pattern, thereby improving the uniformity and stability of the electrode and ensuring excellent electrical performance; compared with traditional electrode preparation processes, the present method simplifies the production process, reduces multiple complex steps and equipment requirements, and by combining flat-plate coating technology, high-precision transfer, water dissolution and high-temperature sintering, the production process becomes more efficient and can meet the needs of large-scale production. The high-temperature sintering step further ensures the stability and durability of the conductive material 5 and improves the reliability and performance of the electrode.

[0052] Example 2 Reference Figure 2 The difference between this embodiment and embodiment 1 is that the method comprises the following steps: S1. Provide a polymer layer 2. In this embodiment, the material of the polymer layer 2 includes but is not limited to one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile. In this embodiment, preferably, the polymer layer 2 is polyvinyl alcohol. Polyvinyl alcohol is soluble in water, which makes the coating and film-forming process more convenient without complicated solvent treatment. In addition, the water-soluble property makes the polyvinyl alcohol easy to clean after use, reducing the burden on the environment. The thickness of the polymer layer 2 is 30-125 μm. In this embodiment, preferably, the thickness of the polymer layer 2 is 35 μm. The concentration of polyvinyl alcohol in the polymer layer 2 is 12-20 wt %. In this embodiment, preferably, the concentration of the polymer layer 2 is 15 wt %. In this embodiment, the polymer layer 2 includes but is not limited to being prepared by a flat coating technique; taking polyvinyl alcohol as the most preferred example, the specific preparation method of the polymer layer 2 includes: a. Prepare polyvinyl alcohol raw materials and solvents, the solvents include but are not limited to deionized water or suitable organic solvents, and corresponding additives such as plasticizers, thickeners or other functional materials can be selected according to actual needs; b. Add the polyvinyl alcohol raw material into an appropriate amount of deionized water, heat and stir until it is completely dissolved to form a uniform polyvinyl alcohol solution, and adjust the concentration of the polyvinyl alcohol solution to ensure that the concentration of the polyvinyl alcohol is between 12-20wt%; c. Apply polyvinyl alcohol solution on a smooth surface (such as glass or plastic film) to control the thickness. You can use a blade, brush or spray gun to control the coating speed and tool gap to achieve the required film thickness of 30-125μm; d. Dry at room temperature to remove some moisture, place the coated polyvinyl alcohol layer in an oven and heat it at 50°C - 70°C to accelerate drying and curing. After drying, the polyvinyl alcohol layer can be naturally peeled off from the smooth surface to form an independent film, thereby obtaining the polymer layer 2.

[0053] The polymer layer 2 prepared by the above method, the polyvinyl alcohol layer in the thickness range of 30-125 μm has good tensile strength and flexibility, and the polyvinyl alcohol with a concentration of 12-20wt% has good solubility in water, making it easy to process and remove; In this embodiment, the water solubility of polyvinyl alcohol can also be changed by adjusting the alcoholysis degree of polyvinyl alcohol or performing a blending modification method so that it can be quickly dissolved at room temperature; specifically, increasing the alcoholysis degree of polyvinyl alcohol (i.e., the degree of alcoholysis of polyvinyl alcohol) can increase its dissolution rate in water, making it easier to be penetrated and dissociated by water molecules, thereby accelerating the dissolution process; blending polyvinyl alcohol with other water-soluble polymers or additives can improve its water solubility. For example, blending with a hydrophilic polymer can enhance the solubility and dissolution rate of polyvinyl alcohol. By optimizing the blending ratio and selecting an appropriate modifier, the solubility properties of polyvinyl alcohol can be adjusted to meet specific application requirements.

[0054] S2, using hot pressing technology, using a mold 7 to hot press a groove 3 corresponding to the desired electrode pattern on the polymer layer 2, to obtain a polymer layer 2 with an electrode pattern. In this embodiment, the substrate of the mold 7 includes but is not limited to a single crystal silicon substrate, a polycrystalline silicon substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate, and an aluminum alloy substrate, and the polymer layer 2 includes but is not limited to forming the groove 3 by hot pressing with a hot press; In this embodiment, the opening width of the electrode pattern of the polymer layer 2 is 3-10 μm, and the aspect ratio is 2:1, that is, the notch width of the groove 3 is 3-10 μm, and the aspect ratio is 2:1; in the precision process of preparing the solar electrode grid line 8, it is very important to accurately control the thickness of the electrode grid line 8 and the width of the patterned opening. These two parameters directly affect the subsequent filling effect of the conductive material 5, the dimensional accuracy of the electrode grid line 8 and the performance of the final battery; the thickness of the polymer layer 2 is in the range of 30-125 μm, and the width of the electrode patterned opening is in the range of 3-1 0μm range, the aspect ratio is 2:1, the above dimensions can take into account the subsequent filling efficiency of the conductive material 5 and the dimensional accuracy requirements of the electrode grid line 8, the narrower opening width helps to reduce the parasitic resistance between the electrode grid lines 8, and improve the current collection efficiency of the battery. At the same time, within this width range, it can also ensure that the conductive material 5 can be fully and evenly filled into the opening to avoid the generation of voids or defects. By precisely controlling the thickness of the polymer layer 2 and the width of the patterned opening, the dimensional accuracy of the electrode grid line 8 can be significantly improved, which helps to reduce performance fluctuations and defective rates caused by dimensional deviations.

[0055] In this embodiment, the hot pressing temperature is 90-150°C. Preferably, the best hot pressing molding conditions are: the hot pressing temperature is 130°C, the hot pressing pressure is 10MPa, and the hot pressing time is 2min. Under these conditions, the groove 3 can be well hot pressed. In this process, the hot pressing temperature range is above the glass transition temperature of polyvinyl alcohol and below its melting point, which avoids discoloration and embrittlement of the polymer layer 2 during the hot pressing process, thereby ensuring the processability, stability and uniformity of the material. Under the above-mentioned best hot pressing molding conditions, the polymer layer 2 can be better shaped to form a precise shape of the groove 3, thereby improving the processing accuracy and the quality of the finished product. By controlling the hot pressing temperature within a safe range, the thermal stress caused by excessively high temperature is reduced, thereby reducing the thermal damage to the material. Specifically, the dried polymer layer 2 is placed on a hot press, and according to the characteristics of the polymer layer 2 and the accuracy of the required electrode pattern, the temperature of the hot press is set to 130°C, the pressure is set to 10MPa and the time is set to 2min. The temperature can soften the polymer layer 2, the pressure can ensure that the pattern of the mold 7 on the hot press can be fully and accurately embossed, and the time can ensure that the details of the pattern are accurately replicated; the dried polymer layer 2 is placed on the heating plate of the hot press, and then the mold 7 is aligned and pressed down. The heating plate is heated to a set temperature, and the mold 7 is pressed into the polymer layer 2 under the pressure of the heating plate to form a groove 3 corresponding to the required electrode pattern; after the hot pressing is completed, the mold 7 and the polymer layer 2 need to be cooled to room temperature. This cooling process allows the polymer layer 2 to maintain its shape in the mold 7, so that the shape and size of the groove 3 are stabilized; after the cooling is completed, the mold 7 is carefully removed from the polymer layer 2, and the pattern of the groove 3 is clearly visible and matches the required electrode pattern; the polymer layer 2 after hot pressing is carefully checked to confirm whether the size and shape of the groove 3 meet the requirements of the micron-level or even nano-level electrode pattern; The shape and size of the groove 3 correspond to the electrode grid line 8. In actual operation, the size and shape of the electrode grid line 8 to be transferred are controlled to reduce the ohmic loss of the electrode grid line 8. The longitudinal cross-sectional shape of the groove 3 includes but is not limited to one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon. In the present embodiment, preferably, the longitudinal cross-sectional shape of the groove 3 is a triangle or a trapezoid. The triangular or trapezoidal longitudinal cross-sectional design helps to change the incident and refraction paths of light, can better capture and guide light, can effectively reduce the reflection loss of light, so that more light is absorbed by the semiconductor material and converted into electrical energy, thereby improving the photoelectric conversion efficiency.

[0056] S3, using a flat coating technique, applying a conductive material 5 on the polymer layer 2, so that the conductive material 5 fills the groove 3, and scraping off excess conductive material 5; Specifically, on the polymer layer 2 where the groove 3 has been formed, the conductive material 5 is evenly applied by a flat coating technology. A suitable conductive material 5 is selected and applied by a flat coating machine or a scraping tool. The conductive material 5 is evenly applied on the polymer layer 2 to ensure that the material can fully fill all the gaps in the groove 3 and cover the entire surface. After coating, a scraper or other tool is used to scrape off excess conductive material 5 on the surface to ensure that the conductive material 5 in the groove 3 is flat and tightly combined with the polymer layer 2. The conductive material 5 includes but is not limited to silver paste, the components of the silver paste include an adhesive, the adhesive is a phenolic resin or an epoxy resin, and the adhesive is used to enhance the bonding between the particles of the silver paste. In this embodiment, the shear strength of the adhesive is 10-30 MPa, and it has excellent bonding performance and chemical resistance; The design of the adhesive can effectively enhance the bonding force between the silver particles in the silver paste, thereby reducing the interruption of the conductive path in the silver paste and improving the conductivity; The polymer layer 2 of polyvinyl alcohol is incompatible with the binder of the silver paste and is non-reactive; the non-reactivity ensures that no chemical change or degradation occurs between the polyvinyl alcohol and the silver paste, and the performance of each of the two is kept stable, which can ensure that each material performs best in its intended application and avoids mutual influence; and the polymer layer 2 can be easily removed by water solubility after processing without affecting the performance of the silver paste; S4, covering the polymer layer 2 on the substrate 6, the polymer layer 2 and the conductive material 5 are adhered to the substrate 6 under a certain temperature and pressure, in this process, including but not limited to, by 90-150°C high temperature and 2-20MPa pressure to make the polymer layer 2 and the conductive material 5 and the substrate 6 adhere to each other, in this embodiment, preferably, the best hot pressing transfer conditions are: hot pressing temperature of 130°C, hot pressing pressure of 10 MPa, hot pressing time of 8min, under which the conductive material 5 and the polymer layer 2 can be well adhered to the substrate 6, and the shape of the conductive material 5 is intact and not deformed; Specifically, clean the surface of the substrate 6 to remove any contaminants or particles, ensure that the surface of the substrate 6 is clean and flat, cover the polymer layer 2 coated with the conductive material 5 on the substrate 6, gently place the polymer layer 2 on the substrate 6, ensure that each part of the conductive material 5 on the polymer layer 2 is in close contact with the surface of the substrate 6, apply a pressure of 10 MPa and a hot pressing temperature of 130° C., press the polymer layer 2 onto the substrate 6, and the pressure needs to be evenly distributed to ensure that the conductive material 5 is completely attached and forms a clear pattern. This step requires ensuring that the pressure is evenly applied to ensure accurate transfer of the conductive material 5. After applying the pressure, maintain the hot pressing between the polymer layer 2 and the substrate 6 for 8 minutes to ensure that the conductive material 5 is fully in contact with and adheres to the substrate 6; In this embodiment, the adhesive can also enhance the bonding between the silver paste particles and the substrate 6. After hot pressing transfer, the conductive material 5 silver paste and the polymer layer 2 will adhere tightly to the substrate 6. At this time, the adhesive in the silver paste can promote the adhesion between the silver paste particles and the substrate 6, thereby improving the bonding strength between the conductive material 5 and the substrate 6, further optimizing the conductive performance, and improving the overall durability and reliability.

[0057] S5, dissolving the polymer layer 2. After the polymer layer 2 is dissolved, the remaining conductive material 5 adheres to the substrate 6; the substrate 6 includes but is not limited to one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate. In this embodiment, preferably, the substrate 6 is a polycrystalline silicon substrate. The polycrystalline silicon substrate has good electronic conductivity and stability, and has good thermal stability and thermal conductivity, and is suitable for the manufacture of various electronic devices, and can be used in the photovoltaic cell used in this application; Specifically, after the transfer work is completed, the polymer layer 2 is dissolved using room temperature water. In this embodiment, the temperature of the room temperature water includes but is not limited to 20-25°C. First, the polymer layer 2 coated with the conductive material 5 is immersed in a container filled with room temperature water. The water temperature should be maintained at room temperature 20-25°C to avoid thermal damage to the conductive material 5 or the substrate 6. During the immersion process, the polymer layer 2 will gradually dissolve in the water. In order to ensure that the polymer layer 2 is completely dissolved, the water can be stirred appropriately or the water temperature can be increased to promote the uniform dissolution process. The time of this process depends on the thickness and material properties of the polymer layer 2. During this period, the dissolution of the polymer layer 2 needs to be checked regularly to ensure that it is completely dissolved. After the polymer layer 2 is completely dissolved, the conductive material 5 pattern will be completely retained on the substrate 6. In order to further ensure the adhesion and stability of the conductive material 5, the surface of the substrate 6 can be rinsed with clean water to remove the tiny fragments of the polymer layer 2 that may remain. Finally, the transferred substrate 6 is dried in the air or by other methods to prepare for the next step of processing.

[0058] S6, sintering the conductive material 5 to form electrode grid lines 8 on the substrate 6. In this embodiment, the process includes but is not limited to sintering the conductive material at a high temperature of 500-1000° C.; Specifically, the substrate 6 coated with the conductive material 5 is placed in a heating furnace or an oven for high-temperature sintering at 500-1000°C. The temperature and time of the sintering process should be set according to the conductive material 5 to ensure that it can be fully sintered at high temperature without damaging the substrate. The sintering time should be set according to the characteristics of the conductive material 5 to ensure that the material has enough time to complete chemical reactions or physical changes at high temperatures to achieve optimal conductivity and adhesion. After sintering, the substrate 6 is allowed to cool naturally to room temperature to avoid thermal stress from damaging the electrode grid lines 8. The sintered electrode grid lines 8 are checked to ensure that their patterns are clear and well adhered. Check whether there is poor conductivity, defects or falling off to ensure that the quality of the electrode grid lines 8 meets the design requirements.

[0059] Example 3 Reference Figure 3 The present application also provides a photovoltaic cell, comprising an electrode grid line 8 prepared by the preparation method described in Example 1 or Example 2; The longitudinal cross-section of the electrode grid line 8 includes but is not limited to a triangle, a trapezoid or a semi-ellipse, and can also be a rectangle, a rhombus, or a polygon. The longitudinal cross-section shape of the electrode grid line 8 can refer to Figure 2 As shown, Figure 2The shapes are only examples and can be other shapes; the vertex angle of the triangle is 20°-60°, the height of the triangle is 10±2μm, the width is 5±1μm, and the aspect ratio of the triangle is 2:1; the base angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2μm, the width is 5±1μm, and the aspect ratio of the trapezoid is 2:1; the height of the semi-ellipse is 10±2μm, the aspect ratio of the semi-ellipse is 2:1, and the width is 5±1μm; the edges of the triangle, trapezoid, and semi-ellipse can better control the propagation direction of light, reduce reflection loss, increase light absorption, and help increase the path length of light inside the battery, thereby increasing light absorption efficiency; In this embodiment, the triangle is an isosceles triangle, the trapezoid is an isosceles trapezoid, and the ellipse is a symmetrical semi-ellipse; the design of the isosceles triangle, the isosceles trapezoid, and the symmetrical semi-ellipse can not only reduce the use of conductive materials, but also reflect and utilize more light energy, and can evenly distribute light on the electrode surface, reduce the concentration effect of light, thereby improving the light capture efficiency, helping to achieve a more uniform current distribution, reducing local resistance, and improving the current output efficiency of the battery, and can provide better structural stability, which helps to maintain the mechanical strength and long-term reliability of the electrode; The photovoltaic cell with electrode grid lines 8 manufactured using this preparation method can significantly improve the photoelectric conversion efficiency of the photovoltaic cell, reduce manufacturing costs, improve production efficiency, and ensure the long-term stability and reliability of the cell through high-precision pattern transfer, excellent electrode quality, simplified process flow and optimized electrode design, which will help promote the application and development of photovoltaic cells.

[0060] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an electrode grid line, characterized in that: The following steps are involved: S1. providing a substrate, and forming a polymer layer on the substrate; S2, using a mold to press out a groove corresponding to the desired electrode pattern on the polymer layer to obtain a template; S3, applying a conductive material on the polymer layer so that the conductive material fills the groove, and scraping off excess conductive material; S4, providing a substrate, covering the template on the substrate, and transferring the polymer layer and the conductive material to the substrate under a certain temperature and pressure; S5, peeling off the base and the polymer layer, and dissolving the polymer layer, leaving the conductive material adhered to the substrate; S6, sintering the conductive material to form the electrode grid line.

2. The method for preparing an electrode grid line according to claim 1, characterized in that: The glass transition temperature of the polymer layer is 70-100° C., and the material of the polymer layer is a water-soluble polymer material.

3. The method for preparing the electrode grid line according to claim 2, characterized in that: The water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.

4. The method for preparing an electrode grid line according to claim 1, characterized in that: The thickness of the polymer layer is 5-20 μm, and the opening width of the electrode pattern is 3-10 μm.

5. The method for preparing the electrode grid line according to claim 1, characterized in that: The conductive material is silver paste, the silver paste includes a binder, and the binder is phenolic resin or epoxy resin.

6. The method for preparing an electrode grid line according to claim 1, characterized in that: In S2, the groove is formed on the polymer layer by hot pressing, and the hot pressing temperature is 90-150°C.

7. The method for preparing an electrode grid line according to claim 1, characterized in that: In S4, a pressure of 2-20 MPa is applied to make the conductive material adhere to the substrate.

8. The method for preparing an electrode grid line according to claim 1, characterized in that: In S5, the polymer layer is dissolved using water at room temperature.

9. The method for preparing an electrode grid line according to claim 1, characterized in that: In S6, the conductive material is sintered at a high temperature of 500-1000°C.

10. The method for preparing an electrode grid line according to claim 1, characterized in that: The longitudinal cross-section of the groove is in the shape of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, or a polygon.

11. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the substrate includes one of polyethylene terephthalate, polyimide, polyethylene terephthalate copolymer, polycarbonate, polypropylene, and polyurethane, and the thickness of the substrate is 120-200 μm.

12. The method for preparing an electrode grid line according to claim 1, characterized in that: The substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

13. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the mold is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy and aluminum alloy.

14. A photovoltaic cell, characterized in that: The electrode grid line comprises the electrode grid line prepared by the preparation method according to any one of claims 1 to 13.

15. The photovoltaic cell according to claim 14, characterized in that: The longitudinal cross-section of the electrode grid line is a triangle, a trapezoid or a semi-ellipse, the top angle of the triangle is 20°-60°, the height of the triangle is 10±2μm, and the aspect ratio of the triangle is 2:1, the base angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2μm, and the aspect ratio of the trapezoid is 2:1, the height of the semi-ellipse is 10±2μm, and the aspect ratio of the semi-ellipse is 2:

1.

16. The photovoltaic cell according to claim 14, characterized in that: The triangle is an isosceles triangle, the trapezoid is an isosceles trapezoid, and the ellipse is a symmetrical semi-ellipse.

Citation Information

Cited By

  • Printing support plate, preparation method of triangular grid line and photovoltaic cell

    CN120287721A

  • Preparation method of photovoltaic cell grid line

    CN121057353A

  • Method for producing a grid line of a photovoltaic cell

    CN121057353B